2013
DOI: 10.4028/www.scientific.net/amm.411-414.2888
|View full text |Cite
|
Sign up to set email alerts
|

The Application Study of Analogy Teaching Method in Automatic Control Principle Teaching

Abstract: For the shortcomings of lacking autonomy, innovative Learning and single experimental way for undergraduate college students, the paper combines the traditional experimental teaching method with computer simulation technology for automatic control principle. The analogy experimental teaching methods can mobilize the enthusiasm of the students, and can solve a single experimental teaching method, insipidity and bad experimental teaching, and can also deep understanding of classroom theory knowledge for undergra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…19 With more attention paid to clinical teaching of nursing, scenario simulation teaching method, as a high-quality teaching method that keeps pace with the times, has been widely applied in nursing teaching. 20 Through scenario simulation, students can carry out nursing practice to effectively improve their learning enthusiasm and consolidate their nursing knowledge as well as operating capabilities. Some studies have reported that the progressive teaching mode can promote the smooth progress of nursing teaching.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…19 With more attention paid to clinical teaching of nursing, scenario simulation teaching method, as a high-quality teaching method that keeps pace with the times, has been widely applied in nursing teaching. 20 Through scenario simulation, students can carry out nursing practice to effectively improve their learning enthusiasm and consolidate their nursing knowledge as well as operating capabilities. Some studies have reported that the progressive teaching mode can promote the smooth progress of nursing teaching.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…However, in the traditional teaching of electromagnetism, teachers often overemphasized electromagnetism as a rigorous knowledge system and maturity structure theory, could not stimulate students' interest in learning, therefore, could not imparted the knowledge to the students effectively [5] . As a teacher, in order to achieve better teaching effect, choosing proper classroom teaching methods is particularly important.…”
Section: Introductionmentioning
confidence: 99%
“…Using this method adequately can inspire students' thinking, provide clues, and draw inferences about other cases from one instance [1] . Electrostatic field and static magnetic field may appear similar in material properties, external performance, quantitative description of the fundamental theorem, energy and other aspects [5][6][7][8][9] . Just grab these characteristics in the classroom teaching and use analogy one by one, teachers can use the students' familiar knowledge of electrostatic field to guide them to master the more difficult static magnetic field knowledge, and improve the teaching efficiency greatly.…”
Section: Introductionmentioning
confidence: 99%